Konsep Pengaturan Hukum Keuangan Negara pada Situasi Darurat dalam Mengatasi Krisis Ekonomi dan Pemulihan Pasca Pandemi Covid-19 di Indonesia - L.M. Alif Pratama (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study examines the concept of state finance regulation in emergency situations to address economic crises and support post-Covid-19 recovery in Indonesia. The pandemic has significantly impacted economic stability, requiring swift and effective legal responses in state finance management. This research employs a normative approach by analyzing legislation related to state finance in emergencies and fiscal policies implemented during the pandemic. The findings reveal that while a legal framework for emergency state finance management exists, its implementation often faces challenges in coordination and accountability. This study recommends strengthening regulations to be more adaptive and proactive in managing state finances during emergencies, as well as enhancing oversight to ensure the effectiveness of sustainable economic recovery. The implications of this research provide a better legal framework for the government to handle future crises.